2012
DOI: 10.1111/j.1461-0248.2012.01798.x
|View full text |Cite
|
Sign up to set email alerts
|

Nematomorph parasites indirectly alter the food web and ecosystem function of streams through behavioural manipulation of their cricket hosts

Abstract: Nematomorph parasites manipulate crickets to enter streams where the parasites reproduce. These manipulated crickets become a substantial food subsidy for stream fishes. We used a field experiment to investigate how this subsidy affects the stream community and ecosystem function. When crickets were available, predatory fish ate fewer benthic invertebrates. The resulting release of the benthic invertebrate community from fish predation indirectly decreased the biomass of benthic algae and slightly increased le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
94
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(103 citation statements)
references
References 54 publications
(116 reference statements)
2
94
0
Order By: Relevance
“…Phenotypic alterations brought about by parasites in their hosts can have several consequences for ecosystems, e.g. by releasing the prey community from predation pressure (Sato et al, 2012) or by affecting the availability of trophic resources to plant and animal communities (Hernandez and Sukhdeo, 2008;Boze et al, 2012). However, although the influence of PIPAs on ecosystem functioning is widely acknowledged (Thomas et al, 1997;Hatcher et al, 2012), we do not know to what extent the ecological impact of a parasite is related to the number of phenotypic alterations it brings about in its host.…”
Section: Introductionmentioning
confidence: 88%
“…Phenotypic alterations brought about by parasites in their hosts can have several consequences for ecosystems, e.g. by releasing the prey community from predation pressure (Sato et al, 2012) or by affecting the availability of trophic resources to plant and animal communities (Hernandez and Sukhdeo, 2008;Boze et al, 2012). However, although the influence of PIPAs on ecosystem functioning is widely acknowledged (Thomas et al, 1997;Hatcher et al, 2012), we do not know to what extent the ecological impact of a parasite is related to the number of phenotypic alterations it brings about in its host.…”
Section: Introductionmentioning
confidence: 88%
“…While most previous work on this system and for aquatic parasites generally has involved laboratory, mesocosm or cage studies (Kiesecker 2002, Schotthoefer et al 2003, ecosystem-scale experiments play an important role in ecology by testing the validity of findings reported from more artificial settings or correlative studies (Tilman 1989, Carpenter et al 1995, 2011, Schindler 1998, Vredenburg 2004, Sato et al 2012. By using a BACI design in an experimentally divided lake, we found that the addition of ;500 Ribeiroia infected snails, which represented a small fraction of the overall snail biomass but a significant increase in parasite cercarial release, resulted in a seven-fold increase in observed infection abundance among larval and metamorphic P. regilla.…”
Section: Discussionmentioning
confidence: 99%
“…The experiment at Hog Lake, which represents one of the few studies to manipulate aquatic parasites at an ecosystem scale (see also Nassi et al 1979, Sato et al 2012, showed that large-scale manipulations of trematode populations are feasible. The study also demonstrated that the relationship between Ribeiroia infection and host pathology varied in strength as a function of study venue (field surveys, lab experiments, and field enclosure cages).…”
Section: Discussionmentioning
confidence: 99%
“…Ecosystem-level effects of invasive predators may extend beyond the habitat where they reside if native prey moves between ecosystems (Baxter et al 2004, Epanchin et al 2010, Sato et al 2012. Affected ecosystems may extend beyond areas adjacent to invaded ecosystems and be hundreds of kilometers away depending on the behavior of the animals that connect them (Reiners and Driese 2004), such as salmon (Holtgrieve and Schindler 2011).…”
Section: Introductionmentioning
confidence: 99%